1992
DOI: 10.1111/j.1600-0447.1992.tb01468.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic‐pituitary‐adrenocortical function in mixed and pure mania

Abstract: There is little information about hypothalamic-pituitary-adrenocortical (HPA) axis function in mania, particularly in mixed states. We therefore investigated HPA function and its relationship to clinical state in 19 hospitalized manic patients meeting Schedule for Affective Disorders and Schizophrenia - Research Diagnostic Criteria for acute manic episodes, compared patients with and without a mixed presentation, and examined correlations between HPA activity and behavior. Data were available from 13-16 patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
1
3

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(43 citation statements)
references
References 26 publications
3
36
1
3
Order By: Relevance
“…10,11,15,18 We present molecular evidence for a reduction (either statistically significant or trending toward significance) in the amplitudes (for BMAL1, REV-ERBa and DBP) and in the overall levels (for DEC2 and DBP) of circadian gene expression in fibroblasts from bipolar patients. BMAL1, the key transcription factor heterodimerizing with CLOCK or NPAS2, drives circadian expression of other clock genes and the clockcontrolled genes.…”
Section: Discussionmentioning
confidence: 79%
See 2 more Smart Citations
“…10,11,15,18 We present molecular evidence for a reduction (either statistically significant or trending toward significance) in the amplitudes (for BMAL1, REV-ERBa and DBP) and in the overall levels (for DEC2 and DBP) of circadian gene expression in fibroblasts from bipolar patients. BMAL1, the key transcription factor heterodimerizing with CLOCK or NPAS2, drives circadian expression of other clock genes and the clockcontrolled genes.…”
Section: Discussionmentioning
confidence: 79%
“…[5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][80][81][82] However, molecular evidence for altered circadian clock in bipolar disorder is still lacking. It has been reported that similar components of the clock machinery underlie rhythmic gene expression in cultured fibroblasts as in the central clock in the SCN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mania with depressive features is more responsive to divalproex than to lithium (Swann et al 1997). A high state of arousal, possibly manifested neurochemically by increased catecholaminergic and hypothalamic-pituitary-adrenocortical function (Swann et al 1992) and behaviorally by irritability, depression, or anger (Swann et al 1986), may reduce the effectiveness of lithium in manic episodes. Identification of fundamental behavioral subtypes that differentially predict response to specific treatments could guide treatment choice.…”
mentioning
confidence: 99%
“…Cortisol may therefore be used as a biological marker of BD. Serotonin increases cortisol release by stimulating 5-HT 1A and 5-HT 2A receptors in hippocampal areas (Nurnberger et al 1990;Swann et al 1992;Vieta et al 1999). Changes in cortisol following challenge with selective 5-HT stimulating agents are possible biological markers to assess brain 5-HT function (Abel and Cleare 1999;Cleare et al 1998).…”
mentioning
confidence: 99%